Fiqh Response to Disease Pandemic (Analysis of the Application of the Rukhshah Concept in the Procedures for the Implementation of Some Worship during the Covid-19 Pandemic) - Helmi Imran; Syamsul Bahri; Fauzul Iqbal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
On March 11, 2020, the World Health Organization (WHO) declared COVID-19 a global pandemic. The decision was issued by the WHO when the corona virus has spread in 118 countries and infected more than 121000 people in Asia, Europe, the Middle East and America. Along with this decision, WHO also issued guidelines on preventing COVID-19, namely by wearing masks, keeping a distance and washing hands. In Indonesia itself, this change has raised a few pros and cons among the people. Some people seem enthusiastic about following guidelines called health protocols, while others seem reluctant to follow them, especially in worship activities. This is evidenced by the emergence of some negative reactions when the scholars, either institutionally or personally issue a fatwa that seems to legitimize the health protocol submitted by the government. In fact, if studied further and objectively, Islam through its jurisprudence has prepared such a concept that accommodates the difficult situations faced by humans. One of the principles of fiqh law is to facilitate the practice of law when humans are in difficult conditions by changing the practice procedures from the usual form to an easier form. This principle is known as rukhshah. When an area is being hit by a disease outbreak, especially since the outbreak has spread globally to the point of being called a pandemic, fiqh of course does not remain silent in responding to the situation. Based on the above, This paper seeks to research and see further whether the current situation related to COVID-19 is included in the category that deserves legal relief or not. This research was conducted by measuring the current situation with the concept of rukhshah which was initiated by the scholars.